2007
DOI: 10.1002/app.26241
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of poly(ϵ‐caprolactone) in poly(ϵ‐caprolactone) and poly(vinyl methyl ether) mixtures

Abstract: ABSTRACT:The morphological development and crystallization behavior of poly(e-caprolactone) (PCL) in miscible mixtures of PCL and poly(vinyl methyl ether) (PVME) were investigated by optical microscopy as a function of the mixture composition and crystallization temperature. The results indicated that the degree of crystallinity of PCL was independent of the mixture composition upon melt crystallization because the glass-transition temperatures of the mixtures were much lower than the crystallization temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In miscible blends, the presence of the noncrystallizable component strongly influences the crystallization behavior of PCL and the resulting morphology. As previously reported, , the spherulitic growth rate of PCL in bulk samples is depressed upon adding a noncrystallizable component due to a decrease in chain mobility and diffusion of the chain segments, while the morphology of PCL crystals becomes more disordered. ,, In ultrathin films, the perturbation is expected to be even more important than in bulk samples due to space confinement. …”
Section: Introductionmentioning
confidence: 72%
“…In miscible blends, the presence of the noncrystallizable component strongly influences the crystallization behavior of PCL and the resulting morphology. As previously reported, , the spherulitic growth rate of PCL in bulk samples is depressed upon adding a noncrystallizable component due to a decrease in chain mobility and diffusion of the chain segments, while the morphology of PCL crystals becomes more disordered. ,, In ultrathin films, the perturbation is expected to be even more important than in bulk samples due to space confinement. …”
Section: Introductionmentioning
confidence: 72%
“…PCL530 with a low T m of 5.5 °C was essentially amorphous in the studied T c range. Similar to other amorphous polymers blended with high-molecular-weight PCL that has substantial χ c and T m higher than 50 °C, PCL530 significantly impeded the crystallization of PCL80k because the dilution of crystallizable polymer chains can influence the free energy of nuclear formation and the transport process of the crystallizable component to the growing front of crystals. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Similar to other amorphous polymers blended with highmolecular-weight PCL that has substantial χ c and T m higher than 50 °C, PCL530 significantly impeded the crystallization of PCL80k because the dilution of crystallizable polymer chains can influence the free energy of nuclear formation and the transport process of the crystallizable component to the growing front of crystals. 20,42,43 Surface Morphology. The spin-coated films and hotcompressed disks of PCL80k and PCL80k/2k (ϕ 80k = 75%) were used to examine the effects of processing method and T c on surface morphology and roughness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A detailed survey of the literature revealed that the spherulitic morphology of semicrystalline PCL and its miscible blends with other noncrystallizable polymers has been studied in great detail 61–64. However, there are very few such studies to date for PCL containing block copolymers 65, 66.…”
Section: Resultsmentioning
confidence: 99%